Noise analysis for CCD-based ultraviolet and visible spectrophotometry - Davenport, John; Hodgkinson, Jane; Saffell, John R.; Tatam, Ralph P. (Optical Society of America, 2015)
We present the results of a detailed analysis of the noise behavior of two CCD spectrometers in common use, an AvaSpec-3648 CCD UV spectrometer and an Ocean Optics S2000 Vis spectrometer. Light sources used include a deuterium UV/Vis lamp and UV and visible LEDs. Common noise phenomena include source fluctuation noise, photoresponse nonuniformity, dark current noise, fixed pattern noise, and read noise. These were identified and characterized by varying light source, spectrometer settings, or temperature. A number of noise-limiting techniques are proposed, demonstrating a best-case spectroscopic noise equivalent absorbance of 3.5×10−4  AU for the AvaSpec-3648 and 5.6×10−4  AU for the Ocean Optics S2000 over a 30 s integration period. These techniques can be used on other CCD spectrometers to optimize performance.
Full-text not yet available due to publisher embargo.